Sunitinib and Imatinib Display Differential Cardiotoxicity in Adult Rat Cardiac Fibroblasts That Involves a Role for Calcium/Calmodulin Dependent Protein Kinase II - McMullen, Calum J.; Chalmers, Susan; Wood, Rachel; Cunningham, Margaret R.; Currie, Susan (Frontiers in Cardiovascular Medicine, 2021)
Tyrosine kinase inhibitors (TKIs) have dramatically improved cancer treatment but are known to cause cardiotoxicity. The pathophysiological consequences of TKI therapy may manifest across different cell types of the heart, yet little of this is understood. Cardiac fibroblasts (CFs) play a pivotal role in the repair and remodelling of the heart following injury, yet their involvement in anti-cancer drug induced cardiotoxicity has been largely overlooked. Here, we examine the direct effects of sunitinib malate and imatinib mesylate on adult rat CF viability, Ca2+ handling and mitochondrial superoxide production. In particular, we investigate whether Ca2+/calmodulin dependent protein kinase II (CaMKII), may be a mediator of TKI-induced effects. CF viability in response to chronic treatment with both drugs was assessed using MTT assays and flow cytometry analysis. Calcium mobilisation was assessed in CFs loaded with Fluo4-AM and CaMKII activation via oxidation was measured via quantitative immunoblotting. Effects of both drugs on mitochondrial function was determined by live mitochondrial imaging using MitoSOX red. Treatment of CFs with sunitinib (0.1-10µM) resulted in concentration-dependent alterations in CF phenotype, with progressively significant cell loss at higher concentrations. Flow cytometry analysis and MTT assays revealed cell apoptosis and necrosis with increasing concentrations of sunitinib. Imatinib treatment resulted in no significant change in cell viability. Sunitinib pre-treatment of CFs increased Angiotensin II-induced intracellular Ca2+ mobilisation and also increased CaMKII activation via oxidation. Live cell mitochondrial imaging using MitoSOX red revealed that both sunitinib and imatinib increased mitochondrial superoxide production in a concentration-dependent manner. This effect in response to both drugs was suppressed in the presence of the CaMKII inhibitor KN-93. Sunitinib and imatinib showed differential effects on CFs, with sunitinib causing marked changes in cell viability at concentrations where imatinib had no effect. Sunitinib caused a significant increase in Angiotensin II-induced intracellular Ca2+ mobilisation and both TKIs caused increased mitochondrial superoxide production. Targeted CaMKII inhibition reversed the TKI-induced mitochondrial damage. These findings highlight a new role for CaMKII in TKI-induced cardiotoxicity, particularly at the level of the mitochondria, and confirm differential off-target toxicity in CFs, consistent with the differential selectivity of sunitinib and imatinib.